Južna postovka Falco naumanni - Šere, Dare (Acrocephalus, 1992)
At Lake Cerknica on 29th April 1989
Keywords: Birds; Cerkniško jezero; Falco naumanni; južna postovka; Ornithology; ornitologija; ptiči; Slovenia; Slovenija